Lumboperitoneal shunts in children: a retrospective study - Mohammad Elbaroody; Basem Ismail Alhayen; Mohamed Eltoukhy; Ahmed Atallah; Hossam Eldin Mostafa; Ahmed Mohamed Alselisly (Egyptian Journal of Neurosurgery)
Abstract Background Lumboperitoneal shunts have been used as a valuable CSF diversion tool in the pediatric age group. This retrospective study reports the indications, outcomes, and possible complications of lumboperitoneal shunts placed in children. Results A total of 19 patients are included in our study. 12 children were males (63.2%) and 7 were females (36.8%). The mean age at LP shunt placement was 5.7 years (6 months–12 years), and most of the children were in the school-age group 11 (57.9%). Idiopathic intracranial hypertension was the most identifiable cause in 9 cases (47.4%), and headache was the most common presenting symptom in 6 patients. The mean follow-up was 36.1 months (17–61 months). Two patients underwent shunt revision due to catheter migration, and three patients (15.8%) developed acquired Chiari malformation for whom the lumboperitoneal shunt was removed and replaced with a ventriculoperitoneal shunt; all the patients are doing well till the last follow-up. Conclusion Lumboperitoneal shunt insertion is a safe and valuable CSF diversion tool in children for various indications on the top of it is idiopathic intracranial hypertension. Long-term follow-up is required for the possibility of acquired Chiari malformation, and the presence of a horizontal–vertical valve could avoid this possible problem.